Economically Sustainable Production Methodologies for Food Grade Colors from Bixa orellana Seed - Seal, Hari Pada; Fakir, Md Solaiman Ali; Borman, N. (Journal of the Bangladesh Agricultural University, 2024)
Food colorants isolated from seeds of Bixa orellana or annatto appears as an unique one for food and drug industries owing to its potential uses. It has a very high commercial and medicinal value in domestic and international markets. This annatto dye is orange red and deep red colored dye present as a thin layer with wax, gum and some other very few compounds on the seed coat of mature fruit. This is nontoxic natural food color insoluble in water but soluble in edible oil and some organic solvents. The principal color pigment in annatto dye is an appocaretenoid molecule known as bixin. Though bixin is insoluble in water but can be converted into water soluble form by careful hydrolysis. These water-soluble forms can be isolated from other associated material by several physical means. As food additives particularly we need both water and edible oil soluble forms. Naturally annatto dye is water insoluble but insoluble in edible oils. So, our objectives of present research work were to separate bixin from other impurities, make it water soluble and considerably stable form for practical use. Accordingly, economic and health friendly extraction and isolation procedures for bixin from seed coat were developed. Economic and health friendly procedures for conversion of bixin into water soluble form and also solid from were developed. Isolated bixin solid is edible oil soluble form. The toxicity of the product was investigated in authorized institute. No toxicity was found. Presence of toxic metallic content in the product was also investigated. All the metals were found to below the international permissible limits for human being. So economically sustainable and health friendly technology for different forms of annatto food colors has developed in the present research work. Thin layer chromatographic study, Ultra violet (UV) and Infrared spectroscopic of the products were also carried out to identify the compounds and their functional nature. J Bangladesh Agril Univ 18(4): 956–962, 2020 https://doi.org/10.5455/JBAU.124601